Витольд Гомбрович o елавянской литературе - Malcew, Leonid (Acta Polono-Ruthenica, 2006)
In the present article Vitold Gombrovich’s views represented in The Diary and in the supplement essay Senkevich are considered. The author proves that psychological and cultural Slavonic basis has a special part in the writer’s conscience. The system of the judgments about Fedor Dostoevsky’s works and historical